The Relationship Between Big Five Personality Traits and Academic Performance of Asian Medical Students - Lauren, Stefani; Nathania, Jocelyn; Wijayanto, Rhendy; Wijaya, Ratna Sari (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Introduction : Personality traits have been shown to influence the individual’s critical thinking, learning strategies, and motivation, resulting in the overall student’s academic performance. Academic performance is an important factor among medical students to ensure their success in long-term medical education, training and work performance as medical doctors. This study aims to evaluate the relationship between personality traits and academic performance among medical students. Methods : The study was conducted among preclinical medical students from the Medical Schools of Pelita Harapan University, Indonesia. The personality traits were assessed using the NEO Five-Factor Inventory-3 (NEO-FFI-3), which consists of 60 items assessing the five personality traits (neuroticism, extraversion, openness, agreeableness, and conscientiousness). The academic performance was evaluated using the cumulative grade point average (CGPA) score. Results : A total of 224 participants were included in this study. The mean age of the participants was 19.8 years old (SD±1.3). Neuroticism was the predominant personality trait among medical students and was found to be negatively associated with CGPA in univariable and multivariable analyses (p<0.05). Conclusion : This study reveals that neuroticism personality traits are prevalent among preclinical medical students and adversely affect their academic performance. Understanding the general personality traits present among medical students and its relationship with academic performance can provide valuable input for further medical education programme development.